2022
DOI: 10.1007/s13364-022-00622-w
|View full text |Cite
|
Sign up to set email alerts
|

Crested porcupine (Hystrix cristata) abundance estimation using Bayesian methods: first data from a highly agricultural environment in central Italy

Abstract: Wildlife abundance estimation is one of the key components in conservation biology. Bayesian frameworks are widely used to adjust the potential biases derived by data collected in the field, as they can increase the precision of model parameter as a consequence of the combination of previous pieces of knowledge (priors) combined with data collected in the field to produce an a-posteriori distribution. Capture-recapture is one of the most common techniques used to assess animal abundance. However, the implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
7
2
Order By: Relevance
“…The use of camera traps for wildlife monitoring has been practiced since the early twentieth century (Chapman 1927), but in recent years, they are becoming one of the mainstream tools used in conservation biology, ranging from the most basic level aimed at assessing species presence at a site (Kays et al 2011;Zaccaroni et al 2020), abundance estimation (Franchini et al 2022;Oberosler et al 2022), and population dynamics studies (Karanth 1995(Karanth , 2006Romani et al 2018;Anile et al 2020;Augugliaro et al 2019Augugliaro et al , 2020 up to the assessment of activity patterns (Andreoni et al 2020;Anile et al 2020) and temporal overlap of different species (Mori et al 2021). This explosion in camera trap use is reflected by the increased number of published papers in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The use of camera traps for wildlife monitoring has been practiced since the early twentieth century (Chapman 1927), but in recent years, they are becoming one of the mainstream tools used in conservation biology, ranging from the most basic level aimed at assessing species presence at a site (Kays et al 2011;Zaccaroni et al 2020), abundance estimation (Franchini et al 2022;Oberosler et al 2022), and population dynamics studies (Karanth 1995(Karanth , 2006Romani et al 2018;Anile et al 2020;Augugliaro et al 2019Augugliaro et al , 2020 up to the assessment of activity patterns (Andreoni et al 2020;Anile et al 2020) and temporal overlap of different species (Mori et al 2021). This explosion in camera trap use is reflected by the increased number of published papers in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Population trend data is lacking (Amori & De Smet, 2016). To the best of our knowledge, no population densities on the border of the distribution range have been reported; only one study estimated porcupine density at the centre of the distribution area based on presence-only data (Franchini et al, 2022). Franchini et al (2022) reported population densities of 0.44 ind•km −2 at a regional scale (17,111 km 2 )…”
Section: Discussionmentioning
confidence: 99%
“…The lack of data on regional and national abundance and densities in Italy makes challenging porcupine population management (https://www.gbif.org/species/5219888). To the best of our knowledge, only one study estimated porcupine abundance in the core area of the distribution range (Franchini et al., 2022). This study used presence‐only data to estimate abundance but did not account for imperfect detection—that is species not detected despite being present—(Dorazio, 2014; Franchini et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations